FINANCIAL TECHNOLOGY (FINTECH): MILLENIALS PRESPECTIVE IN INDONESIA - Sawitri, Ni Nyoman (Dinasti Publisher, 2021)
The purpose of this study is to see from the side of the literature study of existing research results using evidence and perspectives from researchers, The research method used in this study is qualitative with literature studies derived from references to scientific articles that discuss related to the topic, by providing evidence and strengthening with the perspective of researchers, evidence of existing research using qualitative and quantitative methods, so from the point of view of researchers states that it is corroborating and there is also a brief Fintech has become an important part of the lives of the Indonesian millennial generation. By using fintech wisely and developing their financial and technological literacy, millennials can use fintech to make their lives easier and improve their financial well-being.